1968
DOI: 10.3758/bf03342520
|View full text |Cite
|
Sign up to set email alerts
|

Color preference shift in hungry and thirsty pigeons

Abstract: A number of studies have revealed that animals often show marked spontaneous color preferences when responding behaviorally to chromatic stimuli (lise, 1941;Tinbergen & Perdeck, 1950;Curtius, 1954;Hess, 1956;Muntz, 1962; Kear, 1964;Quine & Cullen, 1964; Hailman, 1967). The preference patterns in most cases cannot be related in any simple way to the spectral sensitivity of the receptors (Thompson, in press) and in a given species they appear to vary with the type of behavior the animal responds to the colored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…For 25 and their origins may be ontogenic or phylogenic (e.g., Hess, 1956;Jones, 1954). The relevant literature extends from casual observations of the behavior of adult birds (e.g., Austin, 1974;Blieden, 1974;Brancato, 1974) to experiments that control visual stimulation from the time of hatching (e.g., Kovach, 1971;Mayer &c Hailman, 1976), with color stimuli ranging from painted surfaces or stimulus cards to projected monochromatic sources (e.g., Delius, 1968;Sahgal & Iversen, 1975;Salzen, Lily, & McKeown, 1971;Tracy, 1970). The present experiments illustrate the application of an autoshaping procedure to the study of such preferences.…”
mentioning
confidence: 99%
“…For 25 and their origins may be ontogenic or phylogenic (e.g., Hess, 1956;Jones, 1954). The relevant literature extends from casual observations of the behavior of adult birds (e.g., Austin, 1974;Blieden, 1974;Brancato, 1974) to experiments that control visual stimulation from the time of hatching (e.g., Kovach, 1971;Mayer &c Hailman, 1976), with color stimuli ranging from painted surfaces or stimulus cards to projected monochromatic sources (e.g., Delius, 1968;Sahgal & Iversen, 1975;Salzen, Lily, & McKeown, 1971;Tracy, 1970). The present experiments illustrate the application of an autoshaping procedure to the study of such preferences.…”
mentioning
confidence: 99%
“…For example, many studies use light of different colors to signal the presence of a particular schedule, witlh the rate of responding to the different colors being used as an index of the animal's preference for one ' Delius (1968) and Sahgal and Iversen (1975) have slhown the existence of marked color preferences in the pigeon. Color preferences have also been found in ducklings (Tracy, 1970), and Humphrey (1971) found that monkeys tend to flood their test chambers witlh blue rather than red light.…”
mentioning
confidence: 99%
“…In view of the contradictory results that have been obtained with blue in the begging situation, some authors finding that it was as good a releaser as red, others finding blue to be mediocre, perhaps because of usiiig blues of various intensities (HAILMAN 1969), it seeins likely that its effectiveness is intensity dependent. Elsewhere one of us has in fact suggested that changes in the light-dark adaptation state of the retina, i. e. in the ratio of cone to rod activity, plays a role in determining the response to blue (DELIUS 1968). The red system on the other hand cannot of course be affected by the rods because they are not sensitive to this wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Since the classic study by TINBERGEN and PERDECK (1950) of the colour preferences of gull chicks reacting with the begging response to models of the parental beak, much has been published on spontaneous behavioural colour preferences of birds (e. g. CURTIUS 1954;HESS 1956;TINBEKGEN et al 1962;KEAR 1964;QUINE and CULLEN 1964;HAILMAN 1967;OPPENHEIM 1968;DELIUS 1968). Several aspects of this phenomenon are of special interest, including the nature of the filtering mechanism (MARLEK 1961) that causes the behavioural response to the colour snectrum to be different from the physiological spectral sensitivity recorded at the level of the sensory organs (THOMPSON, in press) and the question of the adaptive value of the preferences in the animal's normal environment (HAILMAN 1968).…”
Section: Introductionmentioning
confidence: 99%